Answer: Last option.
Explanation:
Given the equation:
![(3)/(m+3)-(m)/(3-m)=(m^2+9)/(m^2-9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cv11woxcdr9gk2ai2zujlpqi9uh72uy5om.png)
Follow these steps to solve it:
- Subtract the fractions on the left side of the equation:
![(3(3-m)-m(m+3))/((m+3)(3-m))=(m^2+9)/(m^2-9)\\\\(9-3m-m^2-3m)/((m+3)(3-m))=(m^2+9)/(m^2-9)\\\\(-m^2-6m+9)/((m+3)(3-m))=(m^2+9)/(m^2-9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rs7o8ubar97zs88ztqmyc7186bibnxxxzj.png)
- Using the Difference of squares formula (
) we can simplify the denominator of the right side of the equation:
![(-m^2-6m+9)/((m+3)(3-m))=(m^2+9)/((m+3)(m-3))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gj0x8kspojbturjh9xh3abjsudkad16g5z.png)
- Multiply both sides of the equation by
and simplify:
![((-m^2-6m+9)(m+3)(3-m))/((m+3)(3-m))=((m^2+9)(m+3)(3-m))/((m+3)(m-3))\\\\-m^2-6m+9=((m^2+9)(3-m))/((m-3))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ywg6i809v8szo8x72i5cj293o99esugfh1.png)
- Multiply both sides by
:
![(-m^2-6m+9)(m-3)=((m^2+9)(3-m)(m-3))/((m-3))\\\\(-m^2-6m+9)(m-3)=(m^2+9)(3-m)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/crrtps43unuzobb2ys9nr8a9dne1dkcvcj.png)
- Apply Distributive property and simplify:
![(-m^2-6m+9)(m-3)=(m^2+9)(3-m)\\\\-m^3-6m^2+9m+3m^2+18m-27=3m^2+27-m^3-9m\\\\-m^3-3m^2+27m-27+m^3-3m^2+9m-27=0\\\\-6m^2+36m-54=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4lw6d0wtreoggn8f3o39amwsfimayaj1rc.png)
- Divide both sides of the equation by -6:
![(-6m^2+36m-54)/(-6)=(0)/(-6)\\\\m^2-6m+9=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bjem4az7rbb5ir4nnaunaolx40i2bpse4l.png)
- Factor the equation and solve for "m":
![(m-3)^2=0\\\\m=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/10frd85yfta2qhl51gdeukp0g8qzhvxoys.png)
In order to verify it, you must substitute
into the equation and solve it:
![(3)/(3+3)-(3)/(3-3)=(3^2+9)/(3^2-9)\\\\(3)/(6)-(3)/(0)=(18)/(0)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/23q2dd5d081wq1dg7sh598rzdo4p0wo17u.png)
NO SOLUTION